A catastrophic threat to the already vulnerable towards 2030: Impact of COVID-19 lockdown on livelihood outcome of informal cross border traders in Gweru, Zimbabwe - Dzawanda, Beauty; Matsa, Mark; Nicolau, Melanie (Elsevier Ltd, 2022)
Informal cross-border trade (ICBT) is one significant part of intra-Sub-Saharan African (SSA) trade. This economic activity goes a long way in achieving the Sustainable Development Goals, by providing employment in poor communities, and thus helps in poverty reduction by providing a significant contribution of income into households. For these reasons any disturbance to ICBT in SSA is a serious threat, since it affects the most vulnerable groups of societies. This research examines the impact of COVID-19 on the livelihood outcome of informal cross border traders (ICBTs) in Gweru, Zimbabwe using the case of Global Village Flea Market. The case study design was used, employing qualitative data collection techniques. This research design was chosen as it enabled generation of in-depth understanding of what actually transpired on the ground during the lockdown period. The main sources of data were in-depth interviews with the ICBTs and owner of the flea market. Thirty three ICBTs were selected at the flea market using convenience sampling technique. Results revealed that COVID-19 pandemic had an impact on ICBTs livelihood outcome by causing the global economic retreat of nations, shutting down of borders, shutting down business operations and social contact. There were challenges in acquiring income during this COVID-19 lockdown period since the traders were not allowed to go to work and this presented difficulties in the quest to achieve SDGs 1 and 2 by 2030. Their situation was further worsened by rise in prices of basic commodities which occurred during the lockdown when they were not operating and also by lack of assistance from the government. Sixty one percent (61%) of the respondents who had few savings from the business, that were meant to purchase new stock, had to use these to buy food and pay rentals during the lockdown period. This meant that they no longer had capital to purchase new stock when business resumed. The study recommends the government to provide assistance to ICBTs during the occurrence of such pandemics or situations that result in lockdown of nations.